氧化镍/氧化钛纳米复合材料及其制备方法和储能应用 (2018)
本发明公开了氧化镍/氧化钛纳米复合材料及其制备方法和储能应用，其特征在于：是在经氢化处理的氧化钛纳米管阵列上弥散均匀分布有氧化镍纳米颗粒，制备时首先采用恒电压阳极氧化工艺制备无定型态氧化钛纳米管阵列，然后对其进行氢化处理后，再采用循环伏安电化学沉积方法，在氧化钛纳米管的管壁面上原位沉积氧化镍纳米颗粒，即获得氧化镍/氧化钛纳米管阵列复合材料。本发明所制备的氧化镍/氧化钛纳米复合材料可以通过氢化和电化学活化协同作用共同提高比电容量，是种有较好发展前景的超级电容器储能器件的电极材料。 The invention discloses a nickel oxide/titanium oxide nanocomposite and a preparation method and an energy storage application therefor. The nickel oxide/titanium oxide nanocomposite is characterized in that nickel oxide nanoparticles are uniformly dispersed and distributed on a titanium oxide nanotube array that is subjected to hydrogenation treatment; according to the preparation method, an amorphous state titanium oxide nanotube array is prepared by adopting a constant voltage positive electrode oxidation process; then the amorphous state titanium oxide nanotube array is subjected to the hydrogenation treatment; and then the nickel oxide nanoparticles are deposited on the tube wall surface of the titanium oxide nanotube in an in-situ manner by adopting a cyclic voltamm